Pendidikan PENGELOLAAN KEGIATAN EKSTRAKURIKULER KEAGAMAAN ISLAM DALAM MENINGKATKAN AKHLAK PESERTA DIDIK - Abdul Fattah Nasution; Sunita Bebi; Putri Pitasari Nasution; Nur Latifah Lubis (Cendekia Madani Nusantara, 2024)
Extracurricular jactivities jare jformal jnon-learning jactivities jcarried jout jby jschool jor juniversity jstudents, jgenerally joutside jstandard jcurriculum jstudy jhours. jThis jresearch jaims jto jfind jout jabout jthe jrole jof jreligious jextracurricular jactivities jin jschools jin jimproving jstudents' jmorals. jThis jresearch jmethod jis jdescriptive jqualitative. jThe jdescriptive jqualitative jresearch jmethod jis ja jresearch jmethod jthat jutilizes jqualitative jdata jand jis jdescribed jdescriptively. jIn jhaving jmorals jtowards jAllah, jthese jinclude: jmonotheism jof jAllah jby jaffirming jAllah, jadmitting jthat jthere jis jno jGod jbut jAllah, jRepentance jby jregretting jthe jbad jdeeds jhe jhas jcommitted jand jtrying jto jstay jaway jfrom jthem. jand jreplace jit jwith jgood jdeeds